Determining the fire extinguishing efficiency of compressed air foam with modified additive NH4H2PO4 - Shakhov, Stanislav; Vynohradov, Stanislav; Hryschenko, Dmytry; Melnychenko, Andrii; Grinchenko, Evgen; Knaub, Liudmyla; Maslich, Nataliia; Mohylianets, Tetiana; Pinder, Volodymyr; Pavlyuk, Yuriy (Eastern-European Journal of Enterprise Technologies, 2025)
This study examines the fire extinguishing efficiency of aqueous fire extinguishing agents such as compressed air foam with a modified NH4H2PO4 additive, compressed air foam of standard composition, water, and gel-forming composition. The principal hypothesis assumes that compressed air foam with a modified NH4H2PO4 additive has more effective fire extinguishing properties when extinguishing class A fires in comparison with compressed air foam of standard composition, water, and gel-forming compositions. The task addressed was predetermined by the lack of scientifically substantiated comparative data on the fire extinguishing efficiency of aqueous fire extinguishing agents when extinguishing standardized model fires of class 1A: compressed air foam with a modified NH4H2PO4 additive, compressed air foam of standard composition, water, and gel-forming composition. When using all of the above fire extinguishing agents, successful elimination of combustion was observed. However, the lowest time and mass spent on extinguishing were established precisely for CAF with MA NH4H2PO4. The mass spent on extinguishing the fire by the CAF with NH4H2PO4 is 7% less than the mass of the CAF of standard composition and 52% less than the mass of water. For compressed air foam with MA NH4H2PO4, the extinguishing time was recorded to be 10% less than the time required to extinguish the fire by the CAF of standard composition and 51% less than the time of extinguishing with water. The extinguishing efficiency indicators of the CAF with MA NH4H2PO4, CAF of standard composition, GFC, and water were compared with each other. As a result, the indicator for CAF with MA NH4H2PO4 is Іе.e = 16.5 m2/kg∙s; for CAF of standard composition, Іе.e = 14.03 m2/kg∙s; for GFC, Іе.e = 11.9 m2/kg∙s; for water, Іе.e = 3.94 m2/kg∙s. The results emphasize that the use of MA in the composition of CAF, in particular NH4H2PO4, increases its fire-extinguishing properties when extinguishing class A fires. It has been proven that the fire-extinguishing efficiency of CAF with MA content is 15% higher compared to CAF of standard composition. Compared to GFC, the efficiency is 28% higher; compared to water, 77% higher.